New records of mosquitoes (Diptera: Culicidae) found in phytotelmata in Northern Argentina - Stein, Marina; Alvarez, Carla N.; Alonso, Ana C.; Bangher, Débora N.; Willener, Juana A.; Campos, Raúl E. (Zootaxa, 2018)
The geographical distributions of Culex (Carrollia) secundus, Cx. (Microculex) davisi, Cx. (Phytotelmatomyia) castroi, Cx. (Phy.) renatoi, Lutzia (Lutzia) allostigma, Sabethes (Peytonulus) undosus, Sa. (Sabethoides) glaucodaemon, Toxorhynchites (Lynchiella) bambusicola, Tx. (Lyn.) theobaldi, Wyeomyia (Dodecamyia) aphobema, Wy. (Miamyia) codiocampa and Wy. serratoria (subgenus uncertain) are extended, including new records for four provinces in Argentina and four new records for the country, increasing the number of species known to occur in Argentina from 242 to 246.